1998
DOI: 10.1200/jco.1998.16.5.1940
|View full text |Cite
|
Sign up to set email alerts
|

New combination of the old drugs for elderly patients with small-cell lung cancer: a phase II study of the PAVE regimen.

Abstract: The treatment outcome achieved with PAVE in a phase II study of elderly patients compared favorably with published results of standard regimens in patient populations with better prognostic factors. Because the PAVE regimen can be delivered with good compliance, has acceptable toxicity, and is associated with logistic advantages compared with standard regimens, this protocol is suitable for further investigative trials in elderly patients with SCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…However, the more common situation is of elderly patients who have comorbidity and a poor PS, and cannot tolerate a standard single dose of cisplatin. Westeel et al (1998) and Murray et al (1998) reported that split doses of cisplatin were safely and effectively administered in elderly or frail patients with LD-SCLC. The SPE regimen appeared to be an appropriate treatment for elderly patients with SCLC who cannot tolerate a standard single dose of cisplatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the more common situation is of elderly patients who have comorbidity and a poor PS, and cannot tolerate a standard single dose of cisplatin. Westeel et al (1998) and Murray et al (1998) reported that split doses of cisplatin were safely and effectively administered in elderly or frail patients with LD-SCLC. The SPE regimen appeared to be an appropriate treatment for elderly patients with SCLC who cannot tolerate a standard single dose of cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…The Japan Clinical Oncology Group (JCOG) has reported that carboplatin plus etoposide (CE) is an active and less toxic regimen in elderly patients with SCLC (Okamoto et al, 1999). However, other clinical trials have indicated that the combination chemotherapy of reduced (Souhami et al, 1997) or split doses of cisplatin plus etoposide (SPE) Westeel et al, 1998) can be safely and effectively administered in elderly or poor-risk patients with SCLC. Therefore, we conducted a phase III trial comparing CE with SPE in elderly or poor-risk patients with SCLC.…”
mentioning
confidence: 99%
“…Main retrospective chart reviews on different therapeutic approaches in elderly SCLC patients aged ≥70 Abbreviations: CAV = cyclophosphamide + adriamycin + vincristine; CT = chemotherapy; ED = extensive disease; LD = limited disease; MST = median survival time; OCA = vincristine + cyclophosphamide + doxorubicin; OR = objective response; PE = cisplatin + etoposide; RT = radiotherapy; SCLC = small cell lung cancer. months, respectively) [90]. Ardizzoni et al [89], in a randomized phase II trial including 95 patients, compared two different doses (full versus low) of cisplatin plus etoposide, with G-CSF support in the full-dose arm.…”
Section: New Regimens Specifically Designed For Elderly Patientsmentioning
confidence: 99%
“…Several authors have performed phase II trials employing third-generation combination chemotherapy and designing specific regimens for the elderly [85][86][87][88][89][90][91][92]. A low-dose combination of cisplatin, doxorubicin, vincristine, and etoposide (the PAVE regimen) resulted in impressive RRs (92% in LD-SCLC and 87% in ED-SCLC, with MSTs of 16.2 and 10.8…”
Section: New Regimens Specifically Designed For Elderly Patientsmentioning
confidence: 99%
“…A policy of combination chemotherapy regimes specifically designed for elderly patients has been investigated by the Canadian lung cancer group in Vancouver [68,75]. In the period 1982-1991 elderly or infirm patients with limited SCLC were offered a standard treatment of one-cycle CAV followed 3 weeks later by one-cycle EP plus concurrent thoracic radiotherapy, 20 Gy in 5 fractions or 30 Gy in 10 fractions.…”
Section: Elderly Patientsmentioning
confidence: 99%